Structural analysis of amyloid fibrils modulated by ATP-independent disaggregase and environmental factors - Low, Kimberly Jia Yi (Nanyang Technological University, 2024)
Amyloid fibrils are implicated in various neurodegenerative disorders, including Alzheimer’s disease (AD) and Transforming Growth Factor Beta Induced (TGFBI)- related corneal dystrophy (CD). TGFBI-related CD is a progressive disorder where insoluble protein deposits accumulate in the corneal tissues, resulting in the development of corneal opacity. This thesis aims to elucidate the mechanisms underlying amyloid disaggregation by an ATP-independent chaperone, Lipocalin Prostaglandin D Synthase (L-PGDS), through the construction of atomic model of TGFBI protein (TGFBIp) G623R fibrils using both cryo-electron microscopy and nuclear magnetic resonance techniques. Additionally, we aim to elucidate the structural details of the complex formed between TGFBIp G623R fibrils and L-PGDS, utilizing both solid and solution state NMR data. We will then explore the effectiveness of L-PGDS in disaggregating various performed synthetic fibrils derived from TGFBI protein and amyloid deposits extracted from surgically excised human corneas affected by TGFBI-related CD. Our findings reveal that L-PGDS exhibit selective recognition of structurally frustrated regions within the amyloids, effectively relieving these frustrations and enhancing its binding affinity to amyloid aggregates. This process initiates local restructuring, reducing the persistence length of fibrils and ultimately resulting in the disaggregation of the amyloid structures. Through our mechanistic model, we gain valuable insights into the disaggregation mechanism and alternative energy source utilized by ATP-independent disaggregases for efficient amyloid disassembly. Furthermore, we explore the impact of anticholinergic drugs and air pollutants on the growth rate, morphology, and toxicity of the resulting amyloid fibrils. These findings not only provide a possible link between the exposure of environmental factors and increased risk in amyloid-related diseases but also enhance our understanding of the underlying molecular mechanisms governing the sporadic manifestation of these diseases. Ultimately, these advancements have the potential to significantly improve disease management and prevention strategies for individuals affected by these amyloid-related diseases.